Leishmania amazonensis: Partial purification and study of the biochemical properties of the telomerase reverse transcriptase activity from promastigote-stage - Giardini, M. A.; Fernandez, M. F.; Lira, C. B. B. [UNESP]; Cano, M. I. N. [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Telomeres are protein-DNA complexes that protect chromosome ends from degradation and fusion. In Leishmania spp., telomeric DNA comprises a conserved TTAGGG repeat and is maintained by telomerase. Telomerase is a multisubunit enzymatic complex that ensures the complete DNA replication by adding new telomeric repeats to the G-rich strand. In this report we aimed to purify and study the biochemical properties of Leishmani amazonensis telomerase. In a first trial we used affinity chromatography with antisense 2'-O-methyl oligonucleotide without success since the Leishmania telomerase, similarly to Trypanosoma cruzi enzyme, was not eluted by competition, but instead, it remained bound to the column. Partially purified L. amazonensis telomerase activity was achieved by fractionation of extracts on complementary ion exchange and Heparin columns. Further purification of these fractions on a G-rich telomeric DNA affinity chromatography enriched for telomerase activity. The knowledge of telomerase characteristics in Leishmania could help to develop new strategies to overcome leishmaniasis. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Leishmania amazonensis; Telomerase; TRAP assay; Protein extract; Enzyme purification